(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to compare in vitro fertilization (IVF) outcomes in patients who were administered dual trigger due to OHSS risk in the GnRH antagonist protocol with patients who were administered standard trigger.Materials and Methods: The medical files were retrospectively scanned for all the patients who were admitted to Inonu Unıversity department of obstetrics and gynecology.While the dual trigger group was composed of patients with OHSS risk who were stimulated with GnRH antagonist and received dual trigger(hCG + GnRHa) for final oocyte maturation, the age-matched (20-40) control group consisted of patients who were administered standard trigger (10000 IU uhCG or 500 μgrrhCG and obtained oocyte counts of 500 μgr recombinant hCG). Thetwo groups were compared in terms of the oocyte count, MII oocyte count, and pregnancy and birth outcomes.Results: There was no statistically significant difference between the two groups in terms of age, weight, height, BMI, duration of marriage, presence of previous pregnancy, number of previous parities, number of pre-existing children, number of previous abortus stories, number of smokers, duration of infertility, LH, E2, prolactin, TSH levels, infertility causes, and hCG dose endometrium thickness. The number of oocytes and MII oocytes obtained was significantly higher in the dual trigger group compared to the control group. There was no statistically significant difference between the two groups in terms of the number of pregnancies and number of deliveries. Conclusion: Although the number of oocytes and MII oocytes was higher in the dual trigger group compared to the control group, there was no significant difference in terms of the pregnancy ratios and the number of deliveries.